The effect of lockdown due to COVID-19 on mentally ill patients and their caregivers: a cross sectional study - Janagam, Jayashree; Muraleedharan, K. C.; Gilla, Deepthi; Mohan, N. D. (International Journal Of Community Medicine And Public Health, 2021)
Background: Pandemics are known to cause poor mental well-being and an increased risk of mental disorders. The foremost concern emerging from different aspects of COVID-19 is its impact on mental health. There were many surveys conducted on the general population related to the effect of COVID-19 and few studies on its psychological impact but there is sparse literature on how the containment measures affected the psychiatric patients. Objective of the study was to investigate whether the COVID-19 related lockdown affected the subjective mood and behavior of psychiatric patients and their caregivers. The secondary purpose is to assess the difficulties encountered in procuring medicines and the effect of non-availability of homoeopathic medicines if any. Methods: A cross-sectional survey was conducted on mentally ill patients and their care-givers in the Outpatient Department of Psychiatry in National Homoeopathy Research Institute in Mental Health (NHRIMH), Kottayam. Respondents were evaluated with a specially framed questionnaire containing 22 questions to assess the effect of lockdown on psychiatric patients and their caregivers, who attended the OPD after the COVID-19 related lockdown. The data generated through the study are analysed and presented in this article. Results: Out of the total 548 participants (M-65.9%, F-34.1%) who responded to the survey, 290 (53%) cases expressed that they were distressed to be under lockdown. 26.5% of the clients reported worsening of mental health conditions during lockdown compared to pre-lockdown. 54.2% of the patients found difficulty in procuring homoeopathic medicines during Lockdown. Conclusions: Authorities should consider the ways of limiting the effects of confinement on mentally ill patients and their caregivers by developing strategies to mitigate the adverse consequence of the pandemic.